Autotaxin Expression in Hepatocellular Carcinoma. (3rd September 2018) - Memet, Ilker; Tsalkidou, Evanthia; Tsaroucha, Alexandra K; Lambropoulou, Maria; Chatzaki, Ekaterini; Trypsianis, Gregory; Schizas, Dimitrios; Pitiakoudis, Michael; Simopoulos, Constantinos
ABSTRACT: Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. Despite the important progress observed in liver surgery, the survival rates are discouraging. The aim of this study was to investigate the expression of autotaxin in hepatocellular carcinoma. Materials and Methods: Liver tissues from 28 human hepatocellular carcinomas were evaluated for the expression of autotaxin by immunohistochemistry. The gender, age, histological grade, lymphovascular invasion, number of tumors, levels of serum alpha-fetoprotein (aFP), presence of liver cirrhosis, hepatitis, surgery and survival rates were recorded. Results: Immunohistochemistry confirmed the expression of autotaxin in hepatocellular carcinoma. The histological grade seems to be the only independent predictor of stronger autotaxin expression, as significantly higher levels of autotaxin were detected in histological grades II and III. In addition, levels of autotaxin seem to be the most important independent prognostic factor related to poor survival. There was an eight-fold higher risk of death in patients with high levels of autotaxin compared to patients with low levels. Conclusions: Autotaxin expression in hepatocellular carcinoma could be of great importance. High autotaxin expression in HCC is detected in patients with histological grade II and III. Further, patients with elevated expression levels were found to possess an eight-fold higher risk of death. Autotaxin role in HCC should be further elucidated.